Hepatocytes buried in the cirrhotic livers of patients with biliary atresia proliferate and function in the livers of urokinase‐type plasminogen activator–NOG mice. Issue 9 (4th August 2014) - Suemizu, Hiroshi; Nakamura, Kazuaki; Kawai, Kenji; Higuchi, Yuichiro; Kasahara, Mureo; Fujimoto, Junichiro; Tanoue, Akito; Nakamura, Masato
<x xml:space="preserve">Abstract</x> The pathogenesis of biliary atresia (BA), which leads to end‐stage cirrhosis in most patients, has been thought to inflame and obstruct the intrahepatic and extrahepatic bile ducts. BA is not believed to be caused by abnormalities in parenchymal hepatocytes. However, there has been no report of a detailed analysis of hepatocytes buried in the cirrhotic livers of patients with BA. Therefore, we evaluated the proliferative potential of these hepatocytes in immunodeficient, liver‐injured mice [the urokinase‐type plasminogen activator (uPA) transgenic NOD/Shi‐scid IL2rγnull (NOG); uPA‐NOG strain]. We succeeded in isolating viable hepatocytes from the livers of patients with BA who had various degrees of fibrosis. The isolated hepatocytes were intrasplenically transplanted into the livers of uPA‐NOG mice. The hepatocytes of only 3 of the 9 BA patients secreted detectable amounts of human albumin in sera when they were transplanted into mice. However, human leukocyte antigen–positive hepatocyte colonies were detected in 7 of the 9 mice with hepatocyte transplants from patients with BA. We demonstrated that hepatocytes buried in the cirrhotic livers of patients with BA retained their proliferative potential. A liver that was reconstituted with hepatocytes from patients with BA was shown to be a functioning human liver with a drug‐metabolizing enzyme gene expression pattern that was representative of mature human liver and biliary function, as ascertained by fluorescent dye excretion into the bile canaliculi. These results imply that removing the primary etiology via an earlier portoenterostomy may increase the quantity of functionally intact hepatocytes remaining in a cirrhotic liver and may contribute to improved outcomes. Liver Transpl 20:1127–1137, 2014. © 2014 AASLD.